Social Experimentation, Program Evaluation, and Public Policy 2008
DOI: 10.1002/9781444307399.ch8
|View full text |Cite
|
Sign up to set email alerts
|

Three Conditions under Which Experiments and Observational Studies Produce Comparable Causal Estimates: New Findings from Within‐Study Comparisons

Abstract: This paper analyzes 12 recent within-study comparisons contrasting causal estimates from a randomized experiment with those from an observational study sharing the same treatment group. The aim is to test whether different causal estimates result when a counterfactual group is formed, either with or without random assignment, and when statistical adjustments for selection are made in the group from which random assignment is absent. We identify three studies comparing experiments and regression-discontinuity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
260
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(267 citation statements)
references
References 17 publications
6
260
0
1
Order By: Relevance
“…It is a problem that has mostly been ignored by researchers in the past and mostly plagues non-experimental research (but also experimental research too, for example, when testing mediation in the case of an endogenous mediator). If used correctly, however, causal claims can be made in non-experimental settings, whether using structural equations, two-stage, regression discontinuity, propensity score, or difference-in-differences models (see Antonakis, et al, 2010;Cook, Shadish, & Wong, 2008;Shadish & Cook, 1999;Shadish, Cook, & Campbell, 2002, for in-depth discussion).…”
Section: Trends In Quantitative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a problem that has mostly been ignored by researchers in the past and mostly plagues non-experimental research (but also experimental research too, for example, when testing mediation in the case of an endogenous mediator). If used correctly, however, causal claims can be made in non-experimental settings, whether using structural equations, two-stage, regression discontinuity, propensity score, or difference-in-differences models (see Antonakis, et al, 2010;Cook, Shadish, & Wong, 2008;Shadish & Cook, 1999;Shadish, Cook, & Campbell, 2002, for in-depth discussion).…”
Section: Trends In Quantitative Methodsmentioning
confidence: 99%
“…To conclude, there are a variety of ways in which to use observational data to make clear causal inferences and interested readers should consult more technical literature on this matter (Cook, et al, 2008;Foster, 2010;James, Mulaik, & Brett, 1982;Morgan & Winship, 2007;Pearl, 2000;Rubin, 1974Rubin, , 2008Shadish & Cook, 2009;Shadish, et al, 2002;Shipley, 2000).…”
Section: The Future Of Methodsmentioning
confidence: 99%
“…Two studies are noteworthy. Cook et al (2008) compared estimates from randomized experiments with estimates from observational studies covering a wide range of areas (e.g., education, job training, school dropout prevention). An important feature of this research is that it involved within-study comparisons where the randomized experiments and observational studies shared treatment groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is one reason why their inclusion in policy-relevant meta-analyses has been highly controversial. 2 The empirical literature has shown that, for individual studies, weak methodological designs can lead to severe risks of bias in causal attribution, whereas well-conducted studies that carefully model participation (including IV, RDD and matching) can yield the same results as RCTs at an individual study level (Cook et al 2008, Hansen et al 2011. When comparing average differences across multiple randomised and non-randomised studies using meta-analysis, the evidence is mixed.…”
Section: Risk Of Bias Assessment In Quasi-experimental Designsmentioning
confidence: 99%